Identification and cloning of a novel IL-15 binding protein that is structurally related to the alpha chain of the IL-2 receptor. - Giri, J G (1995)
Interleukin-15 (IL-15) is a novel cytokine of the four-helix bundle family which shares many biological activities with IL-2, probably due to its interaction with the IL-2 receptor beta and gamma (IL-2R beta and gamma c) chains. We report here the characterization and molecular cloning of a distinct murine IL-15R alpha chain. IL-15R alpha alone displays an affinity of binding for IL-15 equivalent to that of the heterotrimeric IL-2R for IL-2. A biologically functional heteromeric IL-15 receptor complex capable of mediating IL-15 responses was generated through reconstruction experiments in a murine myeloid cell line. IL-15R alpha is structurally similar to IL-2R alpha; together they define a new cytokine receptor family. The distribution of IL-15 and IL-15R alpha mRNA suggests that IL-15 may have biological activities distinct from IL-2.